Three years continuous record of the Earth’s magnetic field at Concordia Station (DomeC, Antarctica) - Chambodut, Aude; Di Mauro, Domenico; Schott, Jean-Jacques; Bordais, Pascal; Agnoletto, Lucia; di Felice, Pietro (Annals of Geophysics, 2009)
The magnetic observatory deployed at DomeC, Antarctica, in the French-Italian base known as Concordia hasnow been permanently running for more than three years. This paper focuses on these long-term results whichare more relevant for an observatory intended to provide absolute values of the field. The problems whichemerged in this fairly long record are discussed and solutions suggested to upgrade the observatory to the standardsof an absolute one (i.e. Intermagnet standards).Mailing address: Dr. Aude Chambodut, Ecole et Observatoiredes Sciences de la Terre 5, rue Descartes 67084, StrasbourgCedex, France; e-mail: Aude.Chambodut@unistra.fr